Effects of Material Thickness and Surface Modification of Cross-linked Polyethylene with Poly(2-Methacryloyloxyethyl Phosphorylcholine) on Its Deformation Behavior, Wear Resistance, and Durability Under Repetitive Impact-to-sliding Motion. (June 2017) - Saiga, Kenichi; Kyomoto, Masayuki; Watanabe, Kenichi; Taketomi, Shuji; Kadono, Yuho; Takatori, Yoshio; Tanaka, Sakae; Ishihara, Kazuhiko; Moro, Toru
Abstract 1 : Background: Large femoral heads and thin cross-linked polyethylene (CLPE) acetabular liners are required for preventing dislocation in total hip arthroplasty (THA). However, the wear resistance and durability of thin CLPE liners in severe physiological conditions has not been fully understood. Methods: In this study, we investigated the wear and fatigue properties of untreated CLPE (50 kGy gamma-ray irradiated and annealed) and poly(2-methacryloyloxyethyl phosphorylcholine)-grafted CLPE (PMPC-grafted CLPE) disks that were 3 mm and 6 mm in thickness and subjected to a repetitive impact-to-wear test using a pin-on-disk testing machine. Results: PMPC grafting reduced the gravimetric wear of 3 mm and 6 mm thick CLPE disks, but did not affect volumetric changes at the impact area. However, the volumetric change for 6 mm thick PMPC-grafted CLPE disks in areas subjected to high pressure was significantly less than that for CLPE. The thickness of CLPE did not affect its gravimetric wear, whereas volumetric changes at both bearing and backside surfaces of 3 mm thick disks were significantly larger than those of 6 mm thick disks. The results of finite element analysis indicated that the maximum von Mises stress of 3 mm thick CLPE disks near the backside hole was greater than its yield stress, which resulted in cold flow. Delamination and fracture did not occur for any disks. Discussion: Under impact-to-wear conditions, PMPC grafting and CLPE substrate with sufficient thickness brought wear and fatigue resistance; those are favorable candidates for bearing material under the severe physiological conditions present in reconstructed hip joints. Highlights: We investigated wear and fatigue resistance of PMPC-grafted CLPE disks. PMPC grafting reduced the gravimetric wear under repetitive impact-to-wear testing. PMPC grafting reduced the volumetric change in regions of high contact pressure. Large backside deformation was observed on 3 mm thick disks. PMPC-grafted CLPE with sufficient thickness is appropriate as a bearing material.